Coal Consumption and Economic Growth Nexus: Evidence from Bootstrap Panel Granger Causality Test - Anoruo, Emmanuel (Panoeconomicus, 2017)
This paper explores the causal relationship between coal consumption and economic growth for a panel of 15 African countries using bootstrap panel Granger causality test. Specifically, this paper uses the Phillips-Perron unit root test to ascertain the order of integration for the coal consumption and economic growth series. A bootstrap panel Granger causality test is employed to determine the direction of causality between coal consumption and economic growth. The results provide evidence of unidirectional causality from economic growth to coal consumption. This finding implies that coal conservation measures may be implemented with little or no adverse impact on economic growth for the sample countries as a group. Key words: Coal consumption, Economic growth, Panel causality test. JEL: Q30, Q40, Q50. U radu se ispituje uzročna veza između potrošnje uglja i ekonomskog rasta na osnovu analize 15 afričkih zemalja upotrebom Grangerovog bootstrap panelnog testa uzročnosti. U radu se koristi Phillips-Perronov test jediničnog korena za određivanje nivoa integrisanosti serij apotrošnje uglja i ekonomskog rasta. Grangerov bootstrap panelni test uzročnosti se koristi za određivanje smera uzročnosti između potrošnje uglja i ekonomskog rasta. Rezultati pružaju dokaz o jednosmernoj uzročnosti od ekonomskog rasta ka potrošnji uglja. Nalazi upućuju da mere konzervacije uglja mogu biti implementirane sa malo ili bez štetnog uticaja na ekonomski rast za grupu zemalja iz uzorka. Ključne reči: Potrošnja uglja, Ekonomski rast, Panelni test uzročnosti.